2022
DOI: 10.1177/1329878x221101216
|View full text |Cite
|
Sign up to set email alerts
|

‘Abba Kyari did not die of coronavirus’: Social media and fake news during a global pandemic in Nigeria

Abstract: This study examined the influence of fake news online on how social media users viewed and reacted to the COVID-19 pandemic in Nigeria. Analyses of an online survey ( N = 254) and contents from Twitter users in Nigeria from the hashtags: ‘#coronavirusNigeria’ and ‘#covid19Nigeria’ ( N = 10,408), reveal that social media users in Nigeria used Twitter to inform and educate Twitter users as well as debunking fake news stories about the virus to prevent purveyors of fake news from misleading Twitter users in Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Hence, such deliberate disinformation of the populace via social media needs to be checked. Evidentially, many Nigerians and indeed Africans have tested positive for COVID-19 (Uwalaka, 2022), with many in self-isolation or practising social distancing to avoid spreading the highly contagious disease. It is not a gimmick by those in government to siphon money as 'usual.'…”
Section: Case 7: Fake News About a Dcp In Nigeriamentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, such deliberate disinformation of the populace via social media needs to be checked. Evidentially, many Nigerians and indeed Africans have tested positive for COVID-19 (Uwalaka, 2022), with many in self-isolation or practising social distancing to avoid spreading the highly contagious disease. It is not a gimmick by those in government to siphon money as 'usual.'…”
Section: Case 7: Fake News About a Dcp In Nigeriamentioning
confidence: 99%
“…This study will adopt this definition of fake news as it encapsulates fake news in Nigeria. The inclusion of unintentional sharing of fake news is crucial as many reshare false social media content to help while it ultimately misinforms the recipients (Apuke & Omar, 2021;Wang, McKee, Torbica, & Stuckler, 2019, Uwalaka, 2022. While this study acknowledges that the term, 'fake news' is contested, the study prefers to use 'fake news' as an umbrella word to cover both dis/misinformation.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although Nielsen et al (2020) argue that the concept of infodemics still needs to be explored scientifically, many studies (Valeriani et al 2021;Pennycook et al 2020) in recent years agree that in such situations there is a tendency to spread misinformation in order to undermine public responses to the pandemic and increase polarization. Uwalaka (2022) showed that this was also the case in Nigeria, where the dissemination of problematic information had the consequence of diminishing public trust and adherence to the government's proposed mitigation policies. Coordinated behavior also plays a role as pointed out by a study conducted in Italy that pinpointed a cluster of pages and groups on social media entirely dedicated to skepticism about COVID (Giglietto et al 2022).…”
Section: Introductionmentioning
confidence: 99%